Continuous adductor canal block versus continuous femoral nerve block for postoperative pain in patients undergoing knee arthroplasty: An updated meta-analysis of randomized controlled trials. - Jinyan Gong; Lu Tang; Yuyu Han; Pengcheng Liu; Xue Yu; Fei Wang (PLoS ONE)
Continuous adductor canal block (CACB) is almost a pure sensory nerve block and can provide effective analgesia without blocking the motor branch of the femoral nerve. Thus, the objective of this study was to systematically evaluate the efficacy of CACB versus continuous femoral nerve block (CFNB) on analgesia and functional activities in patients undergoing knee arthroplasty. PubMed, Embase and the Cochrane Central Register of Controlled Trials (from inception to 3 October 2023) were searched for randomized controlled trials (RCTs) that compared CACB with CFNB in patients undergoing knee arthroplasty. Registration in the PROSPERO International prospective register of the meta-analysis was completed, prior to initiation of the study (registration number: CRD42022363756). Two independent reviewers selected the studies, extracted data and evaluated risk of bias by quality assessment. Revman 5.4 software was used for meta-analysis and the summary effect measure were calculated by mean differences and 95% confidence intervals. Eleven studies with a total of 748 patients were finally included. Pooled analysis suggested that both CACB and CFNB showed the same degree of pain relief at rest and at motion at 12 h, 24 h and 48 h in patients undergoing knee arthroplasty. Compared with CFNB, CACB preserved the quadriceps muscle strength better (P<0.05) and significantly shortened the discharge readiness time (P<0.05). In addition, there was no significant difference in opioid consumption, knee extension and flexion, timed up and go (TUG) test, or risk of falls between the two groups. Thus, Compared with CFNB, CACB has similar effects on pain relief both at rest and at motion and opioid consumption for patients undergoing knee arthroplasty, while CACB is better than CFNB in preserving quadriceps muscle strength and shortening the discharge readiness time.